2009
DOI: 10.1007/s12061-009-9039-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effects of a Land Value Tax on Land Development

Abstract: The objective of this research was to evaluate using land value tax as a potential policy tool to moderate sprawling development in Nashville, TN, the nation's most sprawling metropolitan community with a population of one million or more. A land development model was used to evaluate the hypothesis that a land value tax encourages more development closer to areas of preexisting development than does the observed property tax scheme. For the median and lower and upper quartiles of empirical densities, results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Oates & Schwab (1997), for example, found a 47% increase in building permits following the 1979 increase of tax rate on land value in Pittsburgh, Pennsylvania. Cho et al (2011) found that an increase in the SV tax rate increased density and the likelihood of development in Nashville-Davidson County, Tennessee. More recently, modest density effects from increasing the CIV tax rate were found by England et al (2013), who note that "ten percent tax hike would increase the floor-area ratio of the average new home by about 2.2 percent".…”
Section: No Tax: (Rentmentioning
confidence: 98%
“…Oates & Schwab (1997), for example, found a 47% increase in building permits following the 1979 increase of tax rate on land value in Pittsburgh, Pennsylvania. Cho et al (2011) found that an increase in the SV tax rate increased density and the likelihood of development in Nashville-Davidson County, Tennessee. More recently, modest density effects from increasing the CIV tax rate were found by England et al (2013), who note that "ten percent tax hike would increase the floor-area ratio of the average new home by about 2.2 percent".…”
Section: No Tax: (Rentmentioning
confidence: 98%
“…Land development is measured by land value of developable parcels. Cho, Kim and Roberts (2009) indicate that the probability of land development is based on a function of parcel attributes (i.e., individual parcel and neighborhood characteristics, and socioeconomic factors) in general, but especially a tax on land values. Furthermore, many scholars argue that the extent of land development is interactive with, or resulting from, the land values in the community (Cho et al, 2006;Cho and Newman, 2005;Irwin and Bockstael, 2004)…”
Section: Form Of Governmentmentioning
confidence: 99%
“…One way to define the development of land parcel i is to identify whether or not a structure has been built on the parcel during a given period of time (e.g., Cho, Kim, and Roberts 2011;Cunningham 2006). One way to define the development of land parcel i is to identify whether or not a structure has been built on the parcel during a given period of time (e.g., Cho, Kim, and Roberts 2011;Cunningham 2006).…”
Section: Effects Of Land-related Policies 223mentioning
confidence: 99%
“…Defining land development. One way to define the development of land parcel i is to identify whether or not a structure has been built on the parcel during a given period of time (e.g., Cho, Kim, and Roberts 2011;Cunningham 2006). Identifying the development status of a parcel based only on the placement of a structure on the parcel, regardless of the parcel's fragmentation status, presents the problem that structures built on smaller parcels fragmented from a larger parcel (e.g., fragmented parcels within a subdivision from a farmland parcel) are counted as individual land-development decisions, when in fact development of a subdivision represents only one land-development decision by a landowner or a group of landowners.…”
Section: Effects Of Land-related Policies 223mentioning
confidence: 99%